Development of Magnetic Particle Distribution Imaging Using Magnetic Field Reconstruction for Biopsy of the Sentinel Lymph Node - Akari Inagaki (Magnetochemistry, 2021)
The sentinel lymph node is the first lymph-node-draining cancer metastasis. The identification of the sentinel lymph node using magnetic particles and a magnetic sensor has attracted attention in recent years, as this method is less invasive than the conventional method of radiotracer injection. However, the development of a two-dimensional measurement method for sentinel lymph nodes using magnetic nanoparticles remains an issue. In the present study, a method and apparatus for the two-dimensional imaging of magnetic particle distribution were developed to detect a lymph node with magnetic particles concentrated within lymphoid tissues. The method comprises the reconstruction of the magnetic field measured with a high-sensitivity magnetic sensor and with a magnetic detection ability of 2 nT/√Hz at 100 Hz (5 nT/√Hz at 1 Hz). The proposed system measures the two-dimensional magnetic field distribution in an area of up to 25 × 25 mm2 using a coil generating a 0.77 mT external magnetic field applied to the measurement target. The improved spatial resolution of the images makes it possible to use two-dimensional imaging for diagnostics of breast cancer metastases.